UML MODELING OF WEBSITE-BASED BERLIANA LAUNDRY SYSTEM - Ana, Berli (Jurnal Informatika dan Teknik Elektro Terapan, 2025)
Berliana Laundry, a newly launched website-based platform, emerges at a pivotal time coinciding with the significant growth in the laundry industry. This growth has propelled a high demand for laundry services that are fast, efficient, and of high quality. Prioritizing excellence in service and demonstrating a strong commitment to continuously enhancing service quality, Berliana Laundry aims to gain customer trust by prioritizing quality, efficiency, and convenience in its laundry services. The "UML Modeling Journal on Berliana Laundry Website-Based System" is envisioned to serve as a platform for academics and researchers to contribute their knowledge and findings in developing fields related to the laundry industry. Thus, this journal is expected to be a valuable reference for those interested in understanding, developing, and contributing to the dynamic development of the laundry industry.